2002
DOI: 10.1007/s11882-002-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of mold exposure in public schools

Abstract: This paper profiles the impact of mold exposure on the health of students, teachers, and staff in two public elementary schools in Connecticut, and explains how the air quality in each school was tested, and how the health of teachers and students was assessed. It also proposes standards for testing indoor air quality and evaluating the health impact of indoor mold exposure on students, teachers, and staff members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
8
1
2
Order By: Relevance
“…As the measurements included both viable and nonviable particles, viable concentrations (i.e., CFU/m 3 ) would be lower. Unlike (Santilli, 2002) who found Alternaria , Boytrytis , Curvularia , Episoccum , and Stachybotrus exclusively indoors and at high concentrations in three ‘problem schools’, we found no genera that were similarly exclusive and concentrations were low. Indoor bioaerosol concentrations can be highly variable and influenced by many factors, e.g., the life cycle of the organism, season, humidity, window opening, HVAC maintenance, and air filtration.…”
Section: Discussioncontrasting
confidence: 99%
“…As the measurements included both viable and nonviable particles, viable concentrations (i.e., CFU/m 3 ) would be lower. Unlike (Santilli, 2002) who found Alternaria , Boytrytis , Curvularia , Episoccum , and Stachybotrus exclusively indoors and at high concentrations in three ‘problem schools’, we found no genera that were similarly exclusive and concentrations were low. Indoor bioaerosol concentrations can be highly variable and influenced by many factors, e.g., the life cycle of the organism, season, humidity, window opening, HVAC maintenance, and air filtration.…”
Section: Discussioncontrasting
confidence: 99%
“…In the United States, dampness and visible molds in campuses have become an important public health issue for children. 21 However, fungi-related studies in schools are scarce. Th e Massachusetts Department of Public Health has reported a signifi cant association between asthma prevalence and school mold conditions.…”
mentioning
confidence: 99%
“…The presence of elevation on spore count testing can have significance, however, both in terms of total spore count and types of mold present. The author of one study of schools concluded that a building must be considered unhealthy at spore counts over 1000 spores/m 3 [114]. A study of a water-damaged hospital highlights limitations of traditional limited testing.…”
Section: Avoidance and Total Load Reductionmentioning
confidence: 99%